2016
DOI: 10.1039/c5cp08069j
|View full text |Cite
|
Sign up to set email alerts
|

Glass polymorphism in glycerol–water mixtures: II. Experimental studies

Abstract: We here study pressure-induced amorphization and polyamorphic transitions in frozen bulk glycerol–water solutions experimentally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 52 publications
4
69
0
Order By: Relevance
“…It was for example shown that concentrated water:glycerol mixtures form a homogeneous glass at low temperatures, thus avoiding cell-damaging crystallization. 13 However, the study of ternary mixtures including water, cosolvent and protein is more challenging. Despite recent advances (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It was for example shown that concentrated water:glycerol mixtures form a homogeneous glass at low temperatures, thus avoiding cell-damaging crystallization. 13 However, the study of ternary mixtures including water, cosolvent and protein is more challenging. Despite recent advances (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…41-44 3 Recent experimental studies suggest that liquid-liquid transition occurs in a hydrazinium trifluoroacetate solution 45 and various aqueous alcohol solutions. [46][47][48][49][50] Most of the experimental studies measured properties of vitrified aqueous solutions at temperatures near or lower than the crystallization temperature, Tx ~ 150 K, at which amorphous ice crystallizes into ice I by heating.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is supporting evidence for polymorphism in water (1)(2)(3)(4)(5)12), the debate is still continuing for LLT in real water because of the experimental difficulty in accessing it in pure water (recent efforts to access LLT of pure water from the low-temperature side) (4,(13)(14)(15)(16)(17). There have also been efforts to access LLT of water by using aqueous solutions (18)(19)(20)(21)(22)(23)), yet which is often controversial. Thus, an unambiguous example of LLT is highly desirable for establishing its presence firmly.…”
mentioning
confidence: 99%